APOBEC3B is overexpressed in cervical cancer and promotes the proliferation of cervical cancer cells through apoptosis, cell cycle, and p53 pathway - Wei, Zhi; Gan, Jianfeng; Feng, Xuan; Zhang, Mo; Chen, Zhixian; Zhao, Hongbo; Du, Yan (Frontiers in Oncology, 2022)
Objective APOBEC3B (A3B), a member of the APOBEC family of cytidine deaminases, has been gradually regarded as a key cancerous regulator. However, its expression and mechanism in cervical cancer (CC) have not been fully elucidated. This study was to investigate its expression pattern and potential mechanism on the cell cycle, as well as HPV oncogenes in CC. Methods Data from The Cancer Genome Atlas (TCGA) and Gene Expression (GEO) were used to indicate the mRNA expression pattern of A3B in cervical cancer. Western blot assay was used to detect A3B levels in SiHa and Hela cell lines. Immunohistochemistry (IHC) was used to explore A3B protein abundance and sublocation in cervical cancer as well as normal cervical tissues. Based on the Protein atlas (www.proteinatlas.org), A3B expression in the SiHa cell line is lower than in the HeLa cell line. Therefore, the SiHa cell line was used for A3B gene overexpression experiments while the HeLa cell line was used for knockdown experiments. Flow cytometry analysis was used to detect cell apoptosis. Biological function and cancer-related pathways of A3B were conducted using bioinformatics analysis. Results A3B mRNA was significantly overexpressed in cervical cancer in TCGA-cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), GSE67522, and GSE7803. A3B was more highly expressed in cervical cancers than in high-grade squamous intraepithelial lesions and normal controls. A3B expression was found to be progressively activated during cervical cancer development. IHC results showed that A3B was significantly higher in cervical cancer tissues than in normal cervical tissues. A3B plasmid-mediated overexpression experiments and A3B siRNA-mediated knockdown experiments showed that A3B significantly promotes cell proliferation, migration, cell cycle, and chemoresistance in cervical cancer cells by the p53 pathway. GO and KEGG analyses showed that A3B expression was strikingly associated with cell proliferation, apoptosis, and immune-associated pathways. Conclusions Taken together, our study implies that A3B promotes cell proliferation, migration, and cell cycle and inhibits cancer cell apoptosis through the p53-mediated signaling pathway. Moreover, A3B could also contribute to chemoresistance in cervical cancer cells. It may be a potential diagnostic biomarker and therapeutic target for chemoresistant cervical cancers.